2019
DOI: 10.3390/pharmaceutics11110594
|View full text |Cite
|
Sign up to set email alerts
|

Development of a UV-Stabilized Topical Formulation of Nifedipine for the Treatment of Raynaud Phenomenon and Chilblains

Abstract: Raynaud’s Phenomenon is a vascular affliction resulting in pain and blanching of the skin caused by excessive and prolonged constriction of arterioles, usually due to cold exposure. Nifedipine is a vasodilatory calcium channel antagonist, which is used orally as the first-line pharmacological treatment to reduce the incidence and severity of attacks when other interventions fail to alleviate the condition and there is danger of tissue injury. Oral administration of nifedipine, however, is associated with syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
(54 reference statements)
2
6
0
Order By: Relevance
“…Although the use of topical glyceryl trinitrate for Raynaud's phenomenon was suggested as far back as 1951 [56], progress with topical therapies has been very slow. It is hoped that recent systematic reviews on topical nitrates [57,58] herald a wave of new interest, with several publications on topical therapies over the last 3 years [59–61,62 ▪ ,63–65,66 ▪ ]. Wasan et al [62 ▪ ] reported a preclinical study investigating the formulation of a novel nifedipine cream stable to ultraviolet light.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of topical glyceryl trinitrate for Raynaud's phenomenon was suggested as far back as 1951 [56], progress with topical therapies has been very slow. It is hoped that recent systematic reviews on topical nitrates [57,58] herald a wave of new interest, with several publications on topical therapies over the last 3 years [59–61,62 ▪ ,63–65,66 ▪ ]. Wasan et al [62 ▪ ] reported a preclinical study investigating the formulation of a novel nifedipine cream stable to ultraviolet light.…”
Section: Treatmentmentioning
confidence: 99%
“…It is hoped that recent systematic reviews on topical nitrates [57,58] herald a wave of new interest, with several publications on topical therapies over the last 3 years [59–61,62 ▪ ,63–65,66 ▪ ]. Wasan et al [62 ▪ ] reported a preclinical study investigating the formulation of a novel nifedipine cream stable to ultraviolet light. Topical PDE5 inhibitors are also being researched [63,64] and topical econazole nitrate, an antagonist of Transient Receptor Potential Melastatin 8 has been studied in vitro [61,66 ▪ ].…”
Section: Treatmentmentioning
confidence: 99%
“…18 Topical approaches to treatment also merit revisiting, as such, a 'local' approach to treatment could be better tolerated compared with systemic therapies for RP (and also digital ischaemic complications). [65][66][67]…”
Section: Unmet Needs and Challengesmentioning
confidence: 99%
“…After 136 min UV irradiation, the ratio between the absorbances of bands at 224 nm, 276 nm and 310 nm is equal to 2.4:1.6:1. Recently, a band at 310 nm was reported in the case of NIF in methanol, which was exposure to UVA light for 2 h [31]. According to Ref.…”
Section: Resultsmentioning
confidence: 99%